2019
DOI: 10.1038/s41598-019-56584-8
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics and Expression Profile of Transferrin in the Accessory Nidamental Gland of the Bigfin Reef Squid during Bacteria Transmission

Abstract: The accessory nidamental gland (ANG) is a female reproductive organ found in most squid and cuttlefish that contains a consortium of bacteria. These symbiotic bacteria are transmitted from the marine environment and selected by the host through an unknown mechanism. In animals, a common antimicrobial mechanism of innate immunity is iron sequestration, which is based on the development of transferrin (TF)-like proteins. To understand this mechanism of host-microbe interaction, we attempted to characterize the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…In the case of S. lessoniana, this may be the result of host selection. Li et al (2019) indicated that the TF-like protein in the outer layer of the ANG played an important role in the selection of bacteria that are invaginated into the ANG of S. lessoniana. Even though the TF-like protein and lactotransferrin (LTF) may have antimicrobial functions in the host, both are considered to be essential for iron acquisition in Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of S. lessoniana, this may be the result of host selection. Li et al (2019) indicated that the TF-like protein in the outer layer of the ANG played an important role in the selection of bacteria that are invaginated into the ANG of S. lessoniana. Even though the TF-like protein and lactotransferrin (LTF) may have antimicrobial functions in the host, both are considered to be essential for iron acquisition in Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Female S. lessoniana also have an ANG; however, information on the microbial community associated with this ANG is limited. Li et al (2019) hypothesized that as bacteria move from marine environments into the ANG, the transferrin (TF)-like protein of the host may play an essential role in microbial selection. During the maturation process, the ANG gradually transfers bacteria from the outer epithelial cell layer, invaginating bacteria into the ANG and forming tubule structures for bacterial colonies ( Li et al , 2019 ).…”
mentioning
confidence: 99%
“…Immunohistochemical analysis was played according to the procedure reported by Hau-Wen Li 39 . Deparaffinization of the tissue sections was executed using a graded ethanol series, and then 0.3% hydrogen peroxide was used to block endogenous peroxidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…Immunohistochemical analysis. Immunohistochemical analysis was played according to the procedure reported by Hau-Wen Li 35 . Depara nization of the tissue sections was executed using a graded ethanol series, and then 0.3% hydrogen peroxide was used to block endogenous peroxidase activity.…”
Section: Methodsmentioning
confidence: 99%